Oral D-galactose supplementation in PGM1-CDG - Wong, Sunnie Yan-Wai; Poschet, Gernot; Thiel, Christian (Genetics in medicine, 2017)
PurposePhosphoglucomutase-1 deficiency is a subtype of congenital disorders of glycosylation (PGM1-CDG). Previous casereports in PGM1-CDG patients receiving oral D-galactose (D-gal) showed clinical improvement. So far no systematic in vitro and clinical studies have assessed safety and benefits of D-gal supplementation. In a prospective pilot study, we evaluated the effects of oral D-gal in nine patients.MethodsD-gal supplementation was increased to 1.5 g/kg/day (maximum 50 g/day) in three increments over 18 weeks. Laboratory studies were performed before and during treatment to monitor safety and effect on serum transferrin-glycosylation, coagulation, and liver and endocrine function. Additionally, the effect of D-gal on cellular glycosylation was characterized in vitro.ResultsEight patients were compliant with D-gal supplementation. No adverse effects were reported. Abnormal baseline results (alanine transaminase, aspartate transaminase, activated partial thromboplastin time) improved or normalized already using 1 g/kg/day D-gal. Antithrombin-III levels and transferrin-glycosylation showed significant improvement, and increase in galactosylation and whole glycan content. In vitro studies before treatment showed N-glycan hyposialylation, altered O-linked glycans, abnormal lipid-linked oligosaccharide profile, and abnormal nucleotide sugars in patient fibroblasts. Most cellular abnormalities improved or normalized following D-gal treatment. D-gal increased both UDP-Glc and UDP-Gal levels and improved lipid-linked oligosaccharide fractions in concert with improved glycosylation in PGM1-CDG.ConclusionOral D-gal supplementation is a safe and effective treatment for PGM1-CDG in this pilot study. Transferrin glycosylation and ATIII levels were useful trial end points. Larger, longer-duration trials are ongoing.